Arduino music and audio projects - Cook, Mike (Technology in action, 2015)
This book is for musical makers and artists who want to gain knowledge and inspiration for your own amazing creations. ℓ́ℓGrumpy Mikeℓ́ℓ Cook, co-author of several books on the Raspberry Pi and frequent answerer of questions of the Arduino forums, brings you a fun and instructive mix and simple and complex projects to help you understand how the Arduino can work with the MIDI system to create musical instruments and manipulate sound. In Part I youℓ́ℓll find a set of projects to show you the possibilities of MIDI plus Arduino, covering both the hardware and software aspects of creating musical instruments. In Part II, you learn how to directly synthesize a wave form to create your own sounds with Arduino and concludes with another instrument project: the SpoonDuino. Finally, in Part III, youℓ́ℓll learn about signal processing with the Arduino Uno and the Due ℓ́ℓ how to create effects like delay, echo, pitch changes, and realtime backwards audio output. If you want to learn more about how to create music, instruments, and sound effects with Arduino, then get on board for Grumpy Mikeℓ́ℓs grand tour with Arduino Music and Sound Projects.